Technological change, production costs, and supply response - Jha, Dayanatha; Delgado, Christopher L.; Ranade, Chandrashekhar G. (International Food Policy Research Institute, 1988)
The economic argument for intervention in product or factor markets in the agricultural sector rests largely on the need to provide incentives to producers. A reduction in unit cost of production, made possible by technological change, provides another and perhaps more powerful incentive. Therefore, an understanding of the cost relationships under technological change is crucial for a realistic assessment of the need for market interventions.